2016
DOI: 10.1074/mcp.m115.057158
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Phosphoproteomic Screen Uncovers ACLY as Mediator of IL-2-induced Proliferation of CD4+ T lymphocytes

Abstract: Anti-cancer immunotherapies commonly rely on the use of interleukin-2 (IL-2) to promote the expansion of T lymphocytes. IL-2-dependent proliferation is the culmination of a complex network of phosphorylation-driven signaling events that impact on gene transcription through mechanisms that are not clearly understood. To study the role of IL-2 in the regulation of nuclear protein function we have performed an unbiased mass spectrometry-based study of the nuclear phosphoproteome of resting and IL-2-treated CD4 ؉ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 77 publications
(57 reference statements)
2
35
0
2
Order By: Relevance
“…For instance, in our last study focused on deciphering the nuclear phosphoproteome of Tlymphocytes we detected 8,521 unique phosphosites of which more than 10% were not reported in the Phosphosite database and hence were considered as novel [24]. Comparing our phosphosite-panel with the PPSA commercialized by Cell Signaling, we concluded that at present less than 1% of our phosphosites could potentially be detected and therefore verified by the PPSAs available to date.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…For instance, in our last study focused on deciphering the nuclear phosphoproteome of Tlymphocytes we detected 8,521 unique phosphosites of which more than 10% were not reported in the Phosphosite database and hence were considered as novel [24]. Comparing our phosphosite-panel with the PPSA commercialized by Cell Signaling, we concluded that at present less than 1% of our phosphosites could potentially be detected and therefore verified by the PPSAs available to date.…”
mentioning
confidence: 67%
“…Genetic approaches such as site-directed mutagenesis have greatly expanded our knowledge about biological role of the site specific phosphorylations occurring in proteins [22][23][24]. The increasing number of commercially available phosphosite-specific antibodies also allows detecting relatively easily whether a protein is phosphorylated or not on a certain residue that has been previously described.…”
Section: Introductionmentioning
confidence: 98%
“…Horrenbestez, lan-fluxu honen abantailez baliatu gara IL-2k T-zelulen nukleoko proteinen fosforilazio maila nola erregulatzen duen zehazteko [37].…”
Section: Nola Eragiten Du 2-interleukinak T-zelulen Nukleoko Proteineunclassified
“…Guztira fosforilatutako 8521 aminoazido identifikatu eta kuantifikatu ziren egindako esperimentu beraren 3 saiotan [37]. Oro har, fosforilatuta…”
Section: Irudia Il-2k T Linfozitoen Nukleoko Proteinen Fosforilazioaunclassified
“…In these studies, Osinalde and co-workers utilized SILAC labeling and high resolution MS combined with phosphotyrosine immunoprecipitation [91][92][93] and TiO2 enrichment of the phosphopeptides [94,95] to demonstrate that the signaling pathways activated by IL-2 and IL-15 are very similar [94,95]. In addition, they combined antibody-and TiO2-based enrichment with SILAC labeling before MS analysis to show that serine/threonine phosphorylation of the scaffold protein Gab2 is an important step in regulating IL-2 signaling [96] Quantitative phosphoproteomics has also been used to characterize CD8+ CTLs in detail [97,98].…”
Section: Proteomic Studies On T Cellsmentioning
confidence: 99%